2023
DOI: 10.3390/v15051165
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CMV Reactivation to Optimize Care for Critically Ill COVID-19 Patients: A Review on the Therapeutic Potential of Antiviral Treatment

Georgios Schinas,
Vasiliki Moustaka,
Eleni Polyzou
et al.

Abstract: Cytomegalovirus (CMV) reactivation has been linked to adverse clinical outcomes in critically ill patients, with emerging evidence suggesting a potential connection with severe COVID-19. Mechanisms driving this association may include primary lung injury, amplification of systemic inflammation, and secondary immunosuppression. Diagnostic challenges in detecting and assessing CMV reactivation necessitate a comprehensive approach to improve accuracy and inform treatment decisions. Currently, there is limited evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…56,57 However, the question of whether to treat CMV infection in immunocompetent critically ill patients remains contentious. 36,58 Some research supports the curative treatment of clinically confirmed CMV disease, where microbiological evidence aligns with clinical conditions attributed to CMV. 59 Yet, the advantage of preemptive treatment of subclinical viral replication or prophylactic treatment in patients at risk of developing CMV disease is still uncertain.…”
Section: Discussionmentioning
confidence: 98%
“…56,57 However, the question of whether to treat CMV infection in immunocompetent critically ill patients remains contentious. 36,58 Some research supports the curative treatment of clinically confirmed CMV disease, where microbiological evidence aligns with clinical conditions attributed to CMV. 59 Yet, the advantage of preemptive treatment of subclinical viral replication or prophylactic treatment in patients at risk of developing CMV disease is still uncertain.…”
Section: Discussionmentioning
confidence: 98%